2019 IEEE 10th International Workshop on Applied Measurements for Power Systems (AMPS) 2019
DOI: 10.1109/amps.2019.8897794
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Energy and Power Quality On Board Train

Abstract: The European community for over a decade is supporting scientific and technological studies in order to make public transport low environmental impact. The metrological community plays a fundamental role in fostering this improvement. To this purpose, the paper describes the measurement setup and the results of an on-board DC train measurement campaign devoted to the accurate estimate of the energy exchanged between the locomotive and the DC feeder and the electrical energy wasted during the braking stage. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…By looking at Figure 4f, it can be observed that for the first 3 s (265 to 268 s) the train has been stationary (probably waiting on a station), characterized by low traction current with significant distortion. A high level of distortion when trains are near stations has previously been observed in [43]. After the stationary phase, the train has started and accelerated for approximately 2 to 3 s (268 s to 270 s), leaving the station (confirmed by the very low train speed of 27 km/h reported in [35]).…”
Section: Results Of the Proposed Methodsmentioning
confidence: 59%
“…By looking at Figure 4f, it can be observed that for the first 3 s (265 to 268 s) the train has been stationary (probably waiting on a station), characterized by low traction current with significant distortion. A high level of distortion when trains are near stations has previously been observed in [43]. After the stationary phase, the train has started and accelerated for approximately 2 to 3 s (268 s to 270 s), leaving the station (confirmed by the very low train speed of 27 km/h reported in [35]).…”
Section: Results Of the Proposed Methodsmentioning
confidence: 59%
“…To this aim the signals are mostly studied in the time domain using a reference simulation model for confirmation. The measuring setup was preliminarily described in [27] [28]: although the uncertainty assessment has not be completed yet, the used instrumentation and the care in grounding, shielding and EMC in general during the installation indicate that the uncertainty will be dominated by the voltage and current probes.…”
Section: Application To DC Railwaysmentioning
confidence: 99%
“…The measurement set-up is described in [1]. The actual chopped current Ia-chop and Ib-chop is measured directly at the BR resistors Ra and Rb.…”
Section: On-board Measurement Systemmentioning
confidence: 99%